Surface Engineering of Perovskite Oxide for Bifunctional Oxygen Electrocatalysis. Issue 2 (21st September 2018) - Ou, Gang; Yang, Cheng; Liang, Yuwei; Hussain, Naveed; Ge, Binghui; Huang, Kai; Xu, Yushuai; Wei, Hehe; Zhang, Ruoyu; Wu, Hui
Abstract: Perovskite oxide, a low‐cost bifunctional oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) electrocatalyst, has acquired a rapidly growing research interest in the areas of energy conversion and storage, owing to its significant surface structure‐induced catalytic performance. Here, recent progress on the electrocatalytic performance of La0.6 Sr0.4 Co0.2 Fe0.8 O3– δ (LSCF) is built by engineering its surface defect structure through a versatile, effective, and controllable lithium reduction strategy. It is established that the lithium reduction treatment causes the formation of a structurally disordered layer at the surface of LSCF nanoparticles. The treated nanoparticles demonstrate significantly enhanced OER and ORR performance, especially for 5 wt% lithium‐reduced LSCF, whose OER potential decreases from 1.66 to 1.55 V at current density of 10 mA cm −2, and ORR onset potential increases from 0.70 to 0.84 V. This work provides the foundation for the optimization of catalytic performance of perovskite oxide (LSCF). Moreover, such defective materials are promising candidates for energy conversion and storage applications. Abstract : The surface structure of perovskite oxides plays a crucial role on their electrocatalytic performance. Herein, La0.6 Sr0.4 Co0.2 Fe0.8 O3– δ nanopowders with defective surface structure are prepared a controllable, facile, and general lithium reduction method, showing significantly improved electrocatalytic oxygen evolution reaction and oxygen reduction reaction activity and stability owning to the enhanced oxygen exchange kinetics, electrical conductivity, and structural durability.